Research Application of Task-driven Method in Teaching of the Course Operating System - Li Fang; Xu Li (2009 International Conference on Education Technology and Computer, 2009)
On the basis of the analysis of the characteristics of the course operating system, the application of the task-driven method in teaching of this course is researched in this paper. The teaching task design, complement methods and comments on the tasks are discussed, some experiences and attentions are given. The teaching practice shows that the appropriate applications of the task-driven method in teaching of the course operating system can stimulate the enthusiasm of learning and is valuable to provide the innovation ability of the students.